2019
DOI: 10.1002/ange.201911761
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bridged Tetrahydrobenzo[b]azepines and Derivatives through an Aza‐Piancatelli Cyclization/Michael Addition Sequence

Abstract: Herein, we report the preparation of bridged tetrahydrobenzo[b]azepines, which was accomplished through an aza‐Piancatelli cyclization/Michael addition sequence in a one‐pot fashion from readily available precursors. It is noteworthy that a general method to access these scaffolds was hitherto unprecedented. Additionally, the multifaceted aspects of this process have been exemplified through its application to the synthesis of 2‐azabicyclo[3.2.1]octanes and bridged tetrahydrobenzo[b]oxepines, along with post‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…[36][37][38] To this end, hydrogenolysis using palladium on carbon enabled selective cleavage of the benzyloxycarbamate protecting group to give the corresponding aniline, which on treatment with cerium(IV) ammonium nitrate (CAN) gave iminoquinone 31 in 75% yield over two steps. 39 Treatment of 31 with the anion generated from 3-cyanophthalide and LiHMDS resulted in rapid iminoquinone consumption, giving anthraquinone 32 in 86%; 1 H-1 H ROESY analysis of 32 was entirely in keeping with the depicted configuration. Attempts to remove the three PMB ether groups from 33 using Lewis-acidic boron trichloride dimethyl sulfide complex 40 led to degradation of the starting material which also occurred when attempting the deprotection with CAN.…”
Section: Resultsmentioning
confidence: 93%
“…[36][37][38] To this end, hydrogenolysis using palladium on carbon enabled selective cleavage of the benzyloxycarbamate protecting group to give the corresponding aniline, which on treatment with cerium(IV) ammonium nitrate (CAN) gave iminoquinone 31 in 75% yield over two steps. 39 Treatment of 31 with the anion generated from 3-cyanophthalide and LiHMDS resulted in rapid iminoquinone consumption, giving anthraquinone 32 in 86%; 1 H-1 H ROESY analysis of 32 was entirely in keeping with the depicted configuration. Attempts to remove the three PMB ether groups from 33 using Lewis-acidic boron trichloride dimethyl sulfide complex 40 led to degradation of the starting material which also occurred when attempting the deprotection with CAN.…”
Section: Resultsmentioning
confidence: 93%
“…Mechanistic studies further revealed that the introduction of hexafluoroisopropanol (HFIP) [9] could dramatically increase the acidity of the system via the formation of H‐bonding interactions with Ca(NTf 2 ) 2 , thereby facilitating the subsequent transformations even with highly electronically deactivated substrates [10] . By virtue of the established calcium catalysis, a variety of challenging transformations such as arylation, [10d,e] aza‐Piancatelli reaction, [10a,f] hydroacyloxylation, [10c] hydroamidation [10b] have been well addressed thus far. With our efforts, more recently we have also developed an ortho ‐C‐alkenylation/hydroacyloxylation sequence to assembly phthalides benefit from this Ca(NTf 2 ) 2 /HFIP co‐catalytic system [10h] .…”
Section: Introductionmentioning
confidence: 99%